Adsorptive Removal of Dyes from Aqueous Solution by KMnO4-Modified Rice Husk and Rice Straw - Xiaodong Li; Yunjin Li (Journal of Chemistry)
Rice husk (RH) and rice stalk (RS), the abundant biomasses, have been tentatively explored as the renewable biochar which were prepared by means of hydrothermal and activation processes, and the synthetic procedure is quite simple and easy to be scaled up for industrial applications. In this work, the removal of malachite green (MG) was investigated by KMnO4-treated RH and RS as the efficient adsorbents at various experimental conditions. Various operational parameters such as initial dye concentration, adsorbent dosage, and solution temperature in batch systems were investigated on the use of RH and RS. The adsorption isotherm model (Langmuir and Freundlich isotherms), kinetic model (pseudo-first-order, pseudo-second-order, and Elovich models), and the adsorption mechanism (intraparticle diffusion and Boyd models) were studied. It showed that that the Langmuir model and Elovich model are suitable for describing the adsorption process, and the diffusion rate of surface adsorption and the particle diffusion rate jointly affect the reaction rate of adsorption. This facile, efficient, and template-free synthesis strategy holds great promise for preparing novel porous biochar from renewable biomass resources for application in adsorbents.